Ecological Metaphors in the Natoni Oral Tradition of the Atoin Meto Culture in West Timor, Indonesia - Benu, Naniana Nimrod; Prasetyo, Lery; Denil, Mauli (Masyarakat Linguistik Indonesia, 2025)
This research aims to reveal the richness of ecological metaphors in the natoni oral tradition as a local wisdom of the Atoin Meto culture in West Timor, understand the relationship between language and the environment in the Atoin Meto culture, form support for the preservation of Atoin Meto culture and language, namely the Dawan language, contribute to the field of language ecology, and increase awareness about the importance of environmental conservation. This study uses a qualitative ecolinguistic approach to analyze ecological metaphors in the natoni oral tradition of the Atoin Meto culture. Data comes from ten YouTube videos of natoni performances, supplemented by interviews. The metaphors were identified, classified, and analyzed to reflect the community's ecological worldview. The study shows that the lexicons in natoni contain ecological lexicons, including flora, fauna, and natural landscape. These lexicons are metaphorical languages that appear in parallelism which depict the social life of the Atoin Meto. Additionally, these lexicons indicate a close relationship with the Atoin Meto community, nature, and God. This research remains open for further study on other aspects of the ecological lexicon in natoni.